(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
The Workflow models of the patient journey in a Pediatric Emergency Department (PED) seems to be an effective approach to develop an accurate and complete representation of the PED processes. The model developed can drive the collection of comprehensive quantitative and qualitative service delivery and patient treatment data as an evidence base for the PED planning. Our objective in this study is to identify tension indicators and bottlenecks that contribute to over-crowding, the goal is to optimize these paths to improve the quality of the patient handling while mastering the time waiting. The development of this model was based on accurate visits made in the Pediatric Emergency Department (PED) in CHRU of Lille (France). This modeling, which has to represent most faithfully possible the reality of the PED of CHRU of Lille, is necessary. The main aim of this paper is to present the overall design of the proposed Workflow model, emphasizing the simulation results in the normal situation and the crowding situation. Besides, we describe the crowding indicators in PED. Our survey is integrated into the French National Research Agency project, titled: â€œHospital: optimization, simulation and avoidance of strainâ€ (ANR HOST).